The Semantic Meaning of “Head” Component in the Novel “A Farewell to Arms” By Ernest Hemingway - Gadoeva Mavlyuda; Murodova E`tibor (International Journal on Integrated Education, 2022)
This article is devoted to analysis of somatic phrases relating to “head” in the novel “A Farewell to arms” by the writer Ernest Hemingway. The somatic phrases with the word “head” is analyzed deeply and given examples from the novel to identify their exact meanings. All analysis is conducted according to reliable resources of linguistics.